Women farmer group empowerment in Gunungpati Sub-District, Semarang, Indonesia - Fidia Fibriana; Miranita Khusniati; Ni Luh Tirtasari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2020)
The Women Farmer Group in Semarang was established in 2013, and it has been developing small businesses in the processing of local fresh milk into various snack products. However, the selling value has not reached the optimum results since it faces a problem in packagingquality. Therefore, as one of the goals of Tridarma of Indonesian higher education which have directed the university to care about problems in society, an accompaniment to the business was carried out for improving the quality of product packaging. There were three activities conducted, i.e., training; re-designing; and monitoring. The results of the community service showed that the program was highly effective to enhance the understanding of Women Farmer Group members on the importance of product packaging as a strategy of marketing proved by the results of the average posttest score at 80.55. Product testing to consumers shows that the new packaging could increase consumer buying interest in comparison to the old one. Also, with the new packaging, the non-preservative snacks could have a longer storability compared tothe old packaging. In this community service activity, an empowerment model can be obtained and can be further developed.